Control biológico en el cultivo de pimiento (Capsicum annuum L.) con la aplicación de Trichoderma harzianum. - Chiguano Chiguano, Norma Alicia (2022)
This research was carried out at the farm of Don "Alonso Chiguano" which is located in El Carmen parish, La Maná canton, Cotopaxi province. The pepper is one of the crops of great importance so the application of Trichoderma harzianum to prevent the development of fungi or nematodes that cause diseases in plants is useful; this fungus, Trichoderma harzianum, has the ability to take nutrients from pathogenic fungi; compete with them or demote them. For this reason, the research was developed with the general objective of evaluating the biological control in the cultivation of pepper (Capsicum annuum L.) with the application of Trichoderma harzianum; the specific objectives were to verify the effect of Trichoderma harzianum as a biocontroler of Phytophthora capsici, on the pepper crop, the agronomic response of Trichoderma harzianum on the pepper crop was also determined and then the relation of cost was made in the treatments of the application of Trichoderma harzianum with different percentages. Different treatments were established to evaluate the effect of Trichoderma harzianum on the crop, in the respective treatments in study there were a total of 12 plots with an amount of 96 experimental plants at different doses such as T1 0%, T2 5%, T3 10%, and T4 15% of Trichoderma harzianum and a control to determine the efficacy of the product. The variables evaluated were plant height, number of flowers per plant, percentage of incidence, and number of dead plants. Moreover, it was determined how the influence is with the addition of different concentrations of Trichoderma harzianum. A Complete Random Block Design (CRBD) was used and the Tukey Test was used at 0.05% error probability to determine differences between the range of the treatments, being the most effective the T4 Trichoderma harzianum (at 15%) which presented a lower incidence of the pathogen compared to the control during the three applications, as well as in the variable of number of dead plants, registering a value of 0.33% and giving an effective effect. Unlike the control that showed a better percentage of healthy plants with a result of 11.67% and in the variable number of flowers per plant it showed a better effect in relation to the control. It was observed that there is a positive effect regarding the application of Trichoderma harzianum in increasing the number of flowers per pepper crop plants.